2008
DOI: 10.1016/j.powtec.2007.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flocs resistance and reflocculation capacity using the LDS technique

Abstract: In a previous paper we have shown the added value of using LDS to monitor flocculation. It can supply, simultaneously, information on flocs size and structure and enlighten flocculation kinetics and mechanisms. In this paper, LDS is applied to study deflocculation and reflocculation processes of precipitated calcium carbonate (PCC) induced by cationic polyacrylamides, when different types of shear forces are applied. LDS can detect the influence of polymer characteristics and concentration as well as of the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 9 A mathematical model was fitted to the curves enabling the computation of the kinetic 1 constants for both regions (Rasteiro et al, 2008 M a n u s c r i p t using the same conditions as during the flocculation tests, 1400 rpm, at room 1 temperature (22 ºC). The contact time was controlled to be between 16 to 60 min.…”
Section: Polyelectrolytes Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 9 A mathematical model was fitted to the curves enabling the computation of the kinetic 1 constants for both regions (Rasteiro et al, 2008 M a n u s c r i p t using the same conditions as during the flocculation tests, 1400 rpm, at room 1 temperature (22 ºC). The contact time was controlled to be between 16 to 60 min.…”
Section: Polyelectrolytes Characterizationmentioning
confidence: 99%
“…This fit was always good. Table 4 is for the optimum 6 flocculant concentration, defined as the one leading to larger flocs and fastest kinetics 7 (Rasteiro et al, 2008). The optimum flocculant concentration is also indicated in that 8 table.…”
Section: Langmuir Isotherm Fitmentioning
confidence: 99%
“…Biggs et al [3] indicate that scattering patterns at small length scales refer to the light scattered from primary aggregates, whereas at large length scales they correspond to the light scattered from secondary aggregates that resulted from the aggregation of the primary ones. Rasteiro et al [18] also demonstrated that LDS can be used to evaluate the deflocculation and reflocculation processes, when flocs are submitted to mechanical forces (sonication) or to hydrodynamic shearing. In this study we will report how the LDS technique can be used to monitor the flocculation process of precipitated calcium carbonate (PCC) particles induced by cationic polyacrylamides of very high molar mass but with different chain architecture (degree of branching).…”
Section: Open Accessmentioning
confidence: 99%
“…The information obtained is of great importance to understand and predict the flocculation mechanism induced by polyelectrolytes, and thus, to optimize this process. LDS proved to be a convenient tool for the integrated evaluation of flocculant performance in a single test, under turbulent conditions [18].…”
Section: Open Accessmentioning
confidence: 99%
“…High molecular weight and relatively low charge density polymers were shown to promote bridging aggregation, high flocculation rates and less compact flocs. Rasteiro and Garcia [18] applied light diffraction spectroscopy to monitor the flocculation, deflocculation and reflocculation processes of cationic, linear and branched polyelectrolyte/precipitated calcium carbonate mixtures when different types of shear forces were applied. Floc resistance was correlated with floc structures, based on mass fractal dimension data.…”
Section: Introductionmentioning
confidence: 99%